WRITER'S STRATEGIES IN THE INTERCOURSE WITH THE READER IN BELLES-LETTRES - A. S. Komarov (Vestnik MGIMO-Universiteta)
The article is devoted to some strategies aimed at involving the reader into the writer's book by means of making the reader's attitude to its content personal or subjective. In the article it is stated that there are two components which are intrinsic to virtual intercourse between writer and reader. One of the components is the content of the writer's publication while the other is the reader's attitude towards the content suggested. The article shows that the reader's attitude encompasses two processes: the process of self-estrangement from the writer's content and the process of self-involvement into it. In the article, the author analyses these two processes in relation to the content of the book. In the article, the author singles out and gives descriptions of such dimensions of the book's content as its topical and emotional dimension, its depth, human nature dimension and interpersonal relations dimension as well as of strategies used by the writer in order to involve the reader into his writings. The author argues that a successful strategy is based on managing to touch the reader to the quick, i.e. his or her subjectivity, and the result of successfulness can be measured by the reader's readiness and willingness to sink into one of the dimensions suggested. The author of the article comes to the conclusion that signs of the successful strategy can be traced in the reader's return to the intercourse with the writer when he or she rereads the writer's books, repeats or makes references to words, situations or ideas suggested or described by the writer who has grasped the reader's attention in one or several content dimensions.